Ongoing trade facilitation improvement: Its impact on export-oriented small and medium-sized enterprises in Indonesia - Tulus T. H. Tambunan (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2013)
Trade facilitation refers to all measures that can be taken to facilitate cross-border trade flows, but there is no standard formal definition of trade facilitation. This paper examines whether export-oriented MSMEs have access to trade facilitation and how helpful trade facilitation is in supporting exports by MSMEs. Data shows only a small proportion of MSMEs export their products, and the paper makes recommendations on encouraging export activities through increasing awareness and training of MSMEs regarding trade facilitation information, and promotion of information communications technology.
Keywords: F13; 330; Development; Indonesia; SME; Trade; Trade Facilitation